The causal association between genetically regulated 25OHD and chronic obstructive pulmonary disease: A meta-analysis and Mendelian randomization study - Yang, Min; Pang, Bo; Wang, Qiong; Zhang, Zhixin; Niu, Wenquan (Frontiers in Genetics, 2022)
Backgrounds and Objectives: Chronic obstructive pulmonary disease (COPD) is a multifactorial disease under genetic control. We here prepared a meta-analysis to examine the associations of vitamin D binding protein (VDBP) gene rs7041 polymorphism with risk of COPD and changes of circulating 25OHD concentrations. Methods: Literature search, quality assessment, and data extraction were conducted independently by two investigators. Data are expressed as odds ratio (OR) or weighted mean difference (WMD) with 95% confidence interval (CI). Results: Thirteen articles with 3667 participants were meta-analyzed. The rs7041-GT genotype was associated with a 49% reduced COPD risk (OR: 0.51, 95% CI: 0.30 to 0.88, P=0.014) compared to rs7041-TT genotype. Carriers of rs7041-GT genotype had significantly higher concentrations of circulating 25OHD than those with rs7041-TT genotype (WMD: 0.32 ng/ml, 95% CI: 0.09 to 0.55, P=0.006). Under the assumptions of Mendelian randomization and assuming a linear logistic relationship between circulating 25OHD and COPD, an inverse association was noted after using VDBP gene rs7041 polymorphism as an instrument (WMD: -2.07, 95%CI: -3.72 to -0.41, P =0.015). There was a low probability of publication bias. Conclusion: We observed significant associations of VDBP gene rs7041 polymorphism with risk of COPD and changes in circulating 25OHD concentrations. Importantly, we found a causal relation between genetically regulated 25OHD concentrations and COPD risk.